High workload and its application to employee loyalty in indonesian start-up companies - Fahad, Muhammad; Hapsari, Ayuningtyas Yuli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
A company's workforce is one of the most important factors that any company must consider. Human resources are basically in the form of people employed by a company as planners and implementers of all activities and activities carried out by the company with a specific purpose. Good human resources management is required to manage human resources in the company and to ensure that the skills and potential of each human resource are maximized. HR Management is responsible for handling various HR-related matters and works closely with management to further develop the company. The job of personnel management is to create a comfortable working environment by presenting a workload that matches the abilities of each employee. These aspects are intended to increase the loyalty of the company's employees. The purpose of this survey was to determine respondents' responses regarding workload, work environment, and employee retention on PLABS.ID and to determine whether workload and work environment are a factor in employee retention on PLABS.ID. to find out how it affects The research methods used are descriptive and verification methods. The samples used in this survey are all her PLABS.ID employees. Data processing is performed by multiple linear regression, coefficient of determination analysis, and hypothesis testing. The survey results show that there is a significant impact of workload on the employee retention rate of PLABS.ID and work environment the on employee retention rate of PLABS.ID, and both workload and work environment have a significant impact at the same time. It can be said that About employee retention PLABS.ID